Continuity under a different name: The outcome of privatisation in Serbia - Vladan Ivanovic; Vadim Kufenko; Boris Begovic; Nenad Stanisic; Vincent Geloso (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2016)
Normally, privatisation is seen as beneficial. In the case of Serbia, the results are disappointing. This paper considers the failure of privatisation in Serbia - a latecomer in the matter - where privatisation was partly a result of exogenous pressures. In Serbia, a sizeable number of privatised firms were bought by bureaucrats and politicians and all firms were subjected to a period of supervision. We argue that this process of privatisation was designed to allow rentseekers to conserve their privileges through asset stripping and that this explains the failure. In order to do so, we perform empirical analysis of the determinants of liquidation, merger and bankruptcy of privatised firms from 2002 to 2015. We construct a novel data set from primary sources, free of the 'survivorship bias' and containing proxies for various types of owners, indirect signs of asset stripping strategy and a broad range of controls. Our results indicate that firms owned by politicians face significantly higher risks of bankruptcy, especially after the end of supervision.
urn:nbn:de:bsz:100-opus-12545
Keywords: 330; privatisation; asset stripping; logistic regression; survival analysis